Allogeneic stem cell transplant for adults with myelodysplastic syndromes: relevance of pre-transplant disease status. Issue 4 (April 2014) - Busca, Alessandro; Pecoraro, Clara; Giaccone, Luisa; Bruno, Benedetto; Allione, Bernardino; Corsetti, Maria Teresa; Pini, Massimo; Marmont, Filippo; Audisio, Ernesta; D'Ardia, Stefano; Frairia, Chiara; Castiglione, Anna; et al.
Abstract The aim of the present study was to investigate the outcome of 94 adult patients with myelodysplasia (MDS) who received an allogeneic stem cell transplant between January 1995 and September 2010 in two Italian hematology centers. At the time of transplant, 53 patients (56%) had relapsed/refractory disease. The cumulative incidence of grades II–IV acute graft-versus-host disease (GVHD) and chronic GVHD was 33% (95% confidence interval [CI] 21–45%) and 78% (95% CI 66–90%), respectively. The cumulative incidence of transplant-related mortality (TRM) at 100 days was 13% (95% CI 6–21%). The 2-year progression free survival (PFS) and overall survival (OS) were 41% (95% CI 31–51%) and 49% (95% CI 38–59%), respectively. On multivariate analysis, advanced disease stage at transplant was the major independent variable associated with an inferior 2-year PFS (HR 3.66, 95% CI 1.98–6.76) and OS (HR 3.68, 95% CI 1.95–6.93). Use of an alternative donor was an independent variable associated with TRM (HR 3.18, 95% CI 1.31–7.72). In conclusion, our data suggest that disease status at the time of transplant is the major predictor for improved PFS and OS, and treatments required to reach this goal may have value in leading to an improved outcome.